Machine learning for machine health monitoring in IoT - Chen, Wei Jie (2018)
Maintenance has always been an integral part of today’s world. Constant breakage of machines with subsequent repairs have proven to be a huge toll economically. The evolution of maintenance has been present since many decades ago.